The Relationship Between Metabolic Parameters, Age, and Thyroid Status: A Cross-Sectional Study-Based National Survey of Iodine Nutrition, Thyroid Disease - Deng B; Yuan Y; Zhong M; Ren R; Deng W; Duan X (Dove Medical Press, 2021)
Bo Deng,1,* Yi Yuan,1,* Miao Zhong,1,* Rui Ren,1 Wuquan Deng,1 Xiaodong Duan2 1Department of Endocrinology, Chongqing University Central Hospital, Chongqing Emergency Medical Center, Chongqing, 400014, People’s Republic of China; 2Department of Rehabilitation, The Affiliated Hospital of Southwest Medical University, Luzhou, Sichuan, 646000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaodong Duan Email duanxiaodong2032@sina.comAim: The relationship between thyroid status and metabolic factors was investigated as well as iodine nutrition in the general population and among the elderly population.Methods: We performed a cross-sectional survey of 2483 subjects to assess the status of national iodine nutrition and incidence of thyroid disease. The general and elderly populations were divided into normal thyroid function (NTF) and subclinical hypothyroidism (SCH) groups. The anthropometric parameters and biochemical indicators were then analyzed.Results: Overall, 327 participants were diagnosed with thyroid diseases, 73 (22.32%) of whom were 65 years or older. For the general population, compared with the NTF group, individuals in the SCH group were older, presented with higher systolic blood pressure, fasting blood glucose, serum cholesterol, and urinary iodine concentration (all p< 0.05) but lower blood uric acid (UA) (p< 0.05). Linear regression analysis further revealed that age and triglyceride (TG) serum levels positively correlated with serum thyroid-stimulating hormone (TSH) levels. Multiple regression analyses revealed that age, TG, waist circumference (WC), and body mass index were independent predictors for abnormal TSH serum levels. For the elderly population, compared with NTF group, individuals in the SCH group were substantially older (p< 0.05) but presented with lower UA (p< 0.05). Pearson linear regression analysis revealed a positive correlation between age (p=0.003) as well as TG levels (p< 0.001) and serum TSH levels. In contrast, WC (p=0.003) was negatively related to TSH serum levels. Further multiple regression analysis revealed that age, TG, WC and heart rate were independent predictors of blood TSH.Conclusion: The large-scale national study of iodine nutrition, thyroid disease has shown a vital relationship between metabolic indicators and serum TSH levels. Age and metabolic diseases increase the likelihood of developing thyroid diseases, both the general population and among the elderly.Keywords: thyroid function, metabolic status, aging